2016
DOI: 10.1128/jcm.02463-15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Laboratory Assessment of Mycoplasma genitalium Transcription-Mediated Amplification Using Primary Female Urogenital Specimens

Abstract: Following analysis of primary cervix, vagina, and first-void female urine specimens for Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis via commercial transcription-mediated amplification (TMA), residual material was subjected to Mycoplasma genitalium research-use-only TMA. Representation within a 2,478-specimen retrospective study set was established by comparison to a 6-month audit of clinical C. trachomatis TMA (12,999 specimens) on the basis of the C. trachomatis detection rate, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 34 publications
(51 reference statements)
3
34
0
Order By: Relevance
“…genitalium genomic DNA targets (3, 4) and transcription-mediated amplification (TMA) for detection of M. genitalium 16S rRNA (57) has increased our understanding of the epidemiology of M. genitalium, as well as associations between M.…”
Section: Introductionmentioning
confidence: 99%
“…genitalium genomic DNA targets (3, 4) and transcription-mediated amplification (TMA) for detection of M. genitalium 16S rRNA (57) has increased our understanding of the epidemiology of M. genitalium, as well as associations between M.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent report suggests that inclusion of multiple analytes and specimen source collections significantly increases detection of STI carrier status (33). Further investigations may be necessary to indicate targeted demographics (20,(28)(29)(30) should a fully comprehensive screening approach not be advocated in a given locale. Consideration of M. genitalium molecular diagnostics within an STI screening algorithm may ultimately realize public health benefits and improved clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…A community-wide study (with broad demographic and acuity-of-illness coverage) in the same U.S. high-prevalence STI community assessed M. genitalium ASR using 2,478 residual female specimens submitted for routine laboratory screening of C. trachomatis, N. gonorrhoeae, and T. vaginalis (29). The M. genitalium detection rate was 11.4% and exceeded those of the other STI agents (P Յ 0.005).…”
Section: Commercially Developed Rna Amplification Assaysmentioning
confidence: 99%
“…Previous data revealed that repeat TMA analysis performed the same as alternative target testing for confirmation of STI agent detection (19,20). In general, specificity of M. genitalium ASR within a female acute and subacute population was demonstrated by 98.8% concordance between results from M. genitalium ASR and alternative target testing (21). In conclusion, procurement of rectal, pharyngeal, and urine specimens increases overall identification of male STI carrier status.…”
mentioning
confidence: 82%